Down-Turner Syndrome: A Case with Double Monoclonal Chromosomal Abnormality - Gioconda Manassero-Morales; Denisse Alvarez-Manassero; Alfredo Merino-Luna (Case Reports in Pediatrics)
Introduction. The coexistence of Down and Turner syndromes due to double chromosome aneuploidy is very rare; it is even more rare to find the presence of a double monoclonal chromosomal abnormality. Objective. To report a unique case of double monoclonal chromosomal abnormality with trisomy of chromosome 21 and an X ring chromosome in all cells studied; no previous report has been found. Case Report. Female, 28 months old, with pathological short stature from birth, with the following dysmorphic features: tilted upward palpebral fissures, short neck, brachycephaly, and low-set ears. During the neonatal period, the infant presented generalized hypotonia and lymphedema of hands and feet. Karyotype showed 47,X,r(X),+21 [30]. Conclusion. Clinical features of both Down and Turner syndromes were found, highlighting short stature that has remained below 3 z score from birth to the present, associated with delayed psychomotor development. G-banded karyotype analysis in peripheral blood is essential for a definitive diagnosis.